Stability of Polyphenols in Myrtle Berries Syrup, a Traditional Iranian Medicine - Masumeh Mobli; Ismaeil Haririan; Gholamreza Amin; Mohammad Kamalinejad; Mannan Hajimahmoodi (Tehran University of Medical Sciences, 2015)
Myrtus communis L. is a medicinal herb that widely used in Iranian traditional medicine. Myrtle leaves extracts have been studied and a variety of products made from myrtle leaves in Iran and other countries, but only recently, the berries have been the object of scientific interest. In this study, we prepared herbal syrup from myrtle berries aqueous extract and standardized based on total phenols (Folin-Ciocalteu method) and gallic acid (Rhodanine assay) content. Stability tests including phytochemical assay and microbial limit tests were conducted during 3 months of the storage period and pH and viscosity variation of the product were recorded. pH and viscosity of syrup have not been significant changes during 3 months of storage. Evaluation of polyphenol and free gallic acid in myrtle berries syrup was investigated showing that myrtle syrup is microbially and phytochemically stable in the initial 3 months of the storage period.